The ovarian cysts. Analysis of the structure of pathology in women of reproductive age - Шаповал, Ольга Сергiiвна (ScienceRise: Medical Science, 2016)
The problem of treatment of patients with ovarian cysts is the one of main problems in the modern gynecological practice. The use of the results of the different modern methods of diagnostics can essentially shorten the time for setting the clinical diagnosis that is to choose the correct treating tactics in proper time. The aim of work was to analyze the structure of tumor-like formations of ovaries in women of reproductive age. Methods of research. There was carried out the retrospective analysis of 3555 medical histories of patients of reproductive age, who were hospitalized in gynecological department during 2009–2014 and underwent surgical and conservative treatment. The endoscopic optics, made by “Wing” (Russia) was used at laparoscopy. Laparoscopy and histological study of the samples of tissue were carried out according to the standard methods. The data were processed using the statistical program package STATISTICA (StatSoft statistica v.6.0). Results. It was established, that the frequency of ovarian pathology in women of reproductive age in the structure of gynecological pathology is 7,48 %. In the structure of ovarian pathology the frequency of functional cysts is 77,82 %, endometriosis and dermoid cysts – 8,27 %, ovarian cystomas – 4,89 %. Ultrasound examination allows diagnose endometrial ovarian cysts with 100 % exactness, dermoid ovarian cysts – up to 90 %, and in 47.01 % of cases it allows determine the character of functional cysts. In 31 % of patients the ovarian cystomas were endoscopically diagnosed with the further morphological confirmation of diagnosis. As far as the benignant ovarian pathology is in most cases diagnosed just in the active fertile period of women life, all efforts of obstetrician-gynecologist must be directed on timely diagnostics (using invasive methods if necessary) and the treatment of disease that would help to reduce the frequency of cancer and preserve the reproductive potential